Activation of Pyramidal Neurons in Mouse Medial Prefrontal Cortex Enhances Food-Seeking Behavior While Reducing Impulsivity in the Absence of an Effect on Food Intake - Warthen, Daniel M.; Lambeth, Philip S.; Ottolini, Matteo; Shi, Yingtang; Barker, Bryan Scot; Gaykema, Ronald P.; Newmyer, Brandon A.; Joy-Gaba, Jonathan; Ohmura, Yu; Perez-Reyes, Edward; Güler, Ali D.; Patel, Manoj K.; et al. (Frontiers in Behavioral Neuroscience, 2016)
The medial prefrontal cortex (mPFC) is involved in a wide range of executive cognitive functions, including reward evaluation, decision-making, memory extinction, mood, and task switching. Manipulation of the mPFC has been shown to alter food intake and food reward valuation, but whether exclusive stimulation of mPFC pyramidal neurons, which form the principle output of the mPFC, is sufficient to mediate food rewarded instrumental behavior is unknown. We sought to determine the behavioral consequences of manipulating mPFC output by exciting pyramidal neurons in mouse mPFC during performance of a panel of behavioral assays, focusing on food reward. We found that increasing mPFC pyramidal cell output using Designer Receptors Exclusively Activated by Designer Drugs (DREADD) enhanced performance in instrumental food reward assays that assess food seeking behavior, while sparing effects in affect and food intake. Specifically, activation of mPFC pyramidal neurons enhanced operant responding for food reward, reinstatement of palatable food seeking, and suppression of impulsive responding for food reward. Conversely, activation of mPFC pyramidal neurons had no effect on unconditioned food intake, social interaction, or behavior in an open field. Furthermore, we found that behavioral outcome is influenced by the degree of mPFC activation, with a low drive sufficient to enhance operant responding and a higher drive required to alter impulsivity. Additionally, we provide data demonstrating that DREADD stimulation involves a nitric oxide synthase dependent pathway, similar to endogenous muscarinic M3 receptor stimulation, a finding that provides novel mechanistic insight into an increasingly widespread method of remote neuronal control.